STRATEGI KESANTUNAN TINDAK TUTUR POSITIF DAN NEGATIF OLEH KARAKTER DI FILM “LET IT SNOW” (2019) - Anisah Nur Mawaddah; Nurul Fitriani (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
Communication was an activity that usually occurs in the social context. People used communication to engaged each other, with a particular purpose, such as exchanging information, negotiating things, and so on. Basically, when doing communication, we should pay attention to the language politeness, in which it can show our courtesy when talking to each other. Therefore, language politeness was needed in our casual conversation. The purpose of this study was to provide an understanding of two main politeness strategies; the positive and negative politeness which are used by the characters in “Let It Snow” movie. This study used qualitative approach, and content analysis method to conducted the research. The result of the study showed that the characters in “Let It Snow” movie use positive politeness more frequently than the negative one. They used positive politeness strategy to minimize the distance between each other (speaker and listener), while negative politeness is used as a form of respecting to each other.